Assistance in The Planning of Irrigation Channels for Farmers Using Water in Iwoi Sangia Area - Hajia, Muhammad Chaiddir (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
The water for the rice fields comes from the Iwoi Sangia spring. The water flows in irrigation canals that are not feasible so that a lot of water is wasted. Water flows out of the canal through cracks in the walls. This resulted in water not being distributed optimally to the farmers' paddy fields. Through this program, we took the initiative to repair damaged irrigation canals. It is hoped that after the existence of good irrigation canals, water will no longer seep in vain so that irrigation coverage can be wider, irrigation canals become cleaner, and can initiate program plans with government assistance. The method of implementing this activity contains steps to realize the objectives of the community service PKM proposal. Community Service activities, especially the planning of tertiary irrigation channels, were carried out very well and smoothly in accordance with the previous planning activities. This activity begins with interaction with the Village Government and continues with site inspections and field measurements. The result of this community activity is the delineation of irrigation canal plans and budget plans, which will facilitate irrigation work for the Village Government.